ASSESSMENT OF DELETERIOUS EFFECTS OF BISPHENOL A (BPA) ON STEROIDOGENESIS, SPERM COUNT, AND SPERMATOGENESIS IN A MAMMALIAN MODEL - F. Nawaz; Asmatullah; C. Ara (Journal of Animal and Plant Sciences, 2021)
The current study was designed to demonstrate spermatotoxicity of Bisphenol A (BPA) in adult albino male mice, 40 adult albino mice (8 weeks old; weighing 25±5 gm) were randomly categorized into four groups following Completely Randomized Design i.e., G-I (Untreated) G-IV (Vehicle control) G-II (600mg/Kg of B.W) and G-III (300mg/Kg of B.W) respectively. Experimental groups (G-II & G-III) were administered with desired BPA doses (600mg/Kg & 300mg/Kg of B.W) for four weeks routinely through oral gavage, meanwhile, G-I was not given any treatment and G-IV was given soya bean oil. Mice were dissected the next day of the last treatment under deep anesthesia for the collection of blood and testis tissues for further analyses. Microscopic and micrometric examinations showed that BPA had reduced the body as well as testes weight as compared to control. It was also revealed by the biochemical analysis that testosterone hormone level was lowered significantly in BPA exposed groups, which resulted in decreased sperm cell count against control. It severely damaged the seminiferous tubules and interstitial cells. Histological observations showed deformations like Leydig cell apoptosis, oligospermia, tubular destructions in BPA exposed HE stained testis sections. The parameters i.e., body and testes weights, testosterone level, sperm count cells, and Johnson scoring had been found significantly (P ≤ 0.05) altered after BPA intoxication. Numerical data were analyzed statistically via analysis of variance (ANOVA) by using software SPSS (Statistical Program for Social Sciences, version 20) followed by Tukey test to see differences among groups. These results revealed that BPA is a reproductive toxicant in mice.
Keywords: Bisphenol A; Spermatotoxicity; Seminiferous tubules; Histology; Sperm count